Implementasi Media Digital dalam Pembelajaran IPAS Kelas V di Tiga Sekolah Dasar di Sumatera Barat - Gusti, Fariska Ananta; Fitria, Yasika; Putri, Fajria; Fitria, Yanti; Kharisma, Inggria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of digital media in Natural and Social Science (IPAS) learning for Grade V Elementary School based on the Merdeka Curriculum. This research uses a qualitative approach with a multi-site study design conducted at UPT SDN 04 Jaho, UPTD SDN 05 Sarilamak, and UPT SDN 16 Pulau Karam. Data were collected through observation, in-depth interviews, and documentation. The results show that all three schools have integrated digital media such as projectors, interactive PowerPoints, educational videos, and Smart TVs into IPAS learning. Teachers' perceptions of digital media were positive, but challenges remain regarding limited infrastructure and uneven digital competency among teachers. Students showed high enthusiasm for digital-based learning. The effectiveness of digital-based IPAS learning at SDN 04 Jaho reached 89.5% (very effective), SDN 16 Pulau Karam 82.5% (very effective), and SDN 05 Sarilamak 80.25% (effective). This study recommends teacher training, additional digital infrastructure, and strengthening students' digital literacy to optimize digital-based IPAS learning.